Synergistic action of phage phiIPLA-RODI and lytic protein CHAPSH3b: a combination strategy to target Staphylococcus aureus biofilms - Duarte, Ana Catarina (NPJ Biofilms Microbiomes, 2021)
Staphylococcus aureus is considered a priority pathogen due to its increasing acquisition of antibiotic resistance determinants. Additionally, this microbe has the ability to form recalcitrant biofilms on different biotic and inert surfaces. In this context, bacteriophages and their derived lytic proteins may be a forward-looking strategy to help combat staphylococcal biofilms. However, these antimicrobials exhibit individual limitations that may be overcome by combining them with other compounds. This work investigates the combination of a phage-derived lytic protein, CHAPSH3b, and the virulent bacteriophage phiIPLA-RODI. The obtained results show the synergy between both antimicrobials for the treatment of 24-h-old S. aureus biofilms, with greater reductions in viable cell counts observed when phage and lysin are applied together compared to the individual treatments. Time-kill curves and confocal microscopy revealed that the fast antibacterial action of CHAPSH3b reduces the population up to 7 hours after initial exposure, which is subsequently followed by phage predation, limiting regrowth of the bacterial population. Moreover, at least 90% of bacteriophage insensitive mutants are susceptible to the lytic protein. Therefore, CHAPSH3b might help curtail the development of phage resistance during treatment. The combination of the lysin and phiIPLA-RODI also showed promising results in an ex vivo pig skin model of wound infection. Overall, the results of this study demonstrate that the combination of phage-derived lytic proteins and bacteriophages can be a viable strategy to develop improved antibiofilm products.